Поселення зубрицької культуры поблизу с. Городок на Волині - Козак, Д.Н. (Археологія, 1997)
У публікації дається повний аналіз археологічних матеріалів з повністю дослідженого поселення зубрицької культури поблизу с. Городок Луцького р-ну на Волині. Памятники зубрицкой культурной группы выявлены и выделены лишь в 80-х гг., поэтому каждый новый исследованный памятник значительно расширяет источниковедческую базу для освещения истории населения, заселявшего территорию Волыни и Западной Подолии в I—ІІ вв. Поселение в Городке существовало на начальном этапе развития зубрицкой культуры — в конце I — начале II вв. Его материалы, в частности, керамический комплекс, форма и конструкция жилых построек иллюстрируют составные части этой культуры. Основу формирования зубрицких памятников на Волыни составлял зарубинецко-пшеворский симбиоз.
Поселение было небольшим; оно имело длину 90 и ширину 30—40 м. На этой территории размещалось 4 жилища, 8 хозяйственных построек и 25 ям-погребов. Все объекты концентрировались в двух группах. Расстояние между группами составляло 20 м. Анализ плана застройки поселения дает основание предположить, что на нем проживали две разные семьи с отдельными хозяйственными комплексами. В состав одной, очевидно большой патриархальной семьи, входило три малые семьи, в состав второй — одна семья. Очевидно, мы имеем дело с определенным этапом в формировании большой патриархальной семьи, когда к уже существующей семье подселяется новая чужая семья. Их взаимодействие на протяжении последующего периода приводит, вероятно, к сложению единой большой патриархальной семьи. Дальше от этой семьи, очевидно, отпочковывается одна или несколько молодых пар, которые переходят на другие поселения или создают новые поселки. Такой процесс фopмиpoвaния патриархальной семьи у создателей зубрицких памятников прослежен также на материалах поселения у с. Линев на Волыни.
С точки зрения социально-экономического развития городоцкая община является переходной от патриархально-родового к соседскому этапу ее развития. Relics of the Zubritsian cultural group were excavated and identified only in the 80s, that is why each new relic expands greatly the source base for elucidating history of population inhabited the territory of Volyn and Western Podolia in the lst-2nd cent. A. D. A settlement in Gorodok existed at the initial stage of Zubritsian culture development: the lats 1st and early 2nd cent. A. D. Findings from this settlement, in particular, a set of pottery, shape and design of dwellings demonstrate constituent parts of this culture. Formation of Zubritsian relics in Volyn was based on the symbiosis of Zarubinets and Pshevorian cultures.
The settlement was not large: 90 m long and 30—40 m wide. In that territory there were 4 dwellings, 8 household buildings and 25 pits-cellars. All objects were concentrated in two groups. The distance between the groups was 20 m. The analysis of the building plan gives grounds to suppose that two families lived in the settlement, each having its own household assemblage. One family, probably large and patriarchal in composition, embraced three small families; the second family was alone in composition. Most likely it was a definite stage in formation of a large patriarchal family when a strange family settled to a family which already existed. Their interaction in the period that followed had, probably, led to formation of a large patriarchal family. In the course of time either one or several young pairs detached from the large family, formed their own families, went to other settlements or built new ones. This process of formation of the patriarchal family in creators of the Zubritsian relics has been also traced on findings from the settlement near vil. Linev in Volyn.
In the aspect of socio-economic development, the Gorodok community is a transitional one from the patriarchal-tribal to the neighbor stage of community development.